Effect of Combination of Kinesio Tapping and Stretching Exercise on Changes in Flexibility in Low Back Pain Patients - Fajar Sumpena; Nurul Halimah; Angria Pradita; Achmad Fariz (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Low back pain includes various types of pain such as nociceptive, neuropathic, and neoplastic, which are often interrelated. The various elements that make up the lumbar spine, such as soft tissues, vertebrae, zygapophyseal and sacroiliac joints, intervertebral discs, and neurovascular structures, can experience different stresses. Each of these elements, either individually or together, can contribute to the onset of low back pain. This study aims to determine the effect of a combination of Kinesio tapping and stretching exercises on changes in flexibility in patients with low back pain at Koesnadi Bondowoso Hospital. This research is quasi-experimental with a one-group pretest-posttest design. This study was conducted at Koesnadi Bondowoso Hospital from June to July 2024. The study population was all patients with low back pain with decreased flexibility at Koesnadi Bondowoso Hospital. The study sample was patients with low back pain with decreased flexibility at Koesnadi Bondowoso Hospital who met the inclusion and exclusion criteria totaling 32 samples. Primary data were collected through direct interviews followed by examination. Data analysis using the Wilcoxon test. Based on the results of the analysis, it is known that there is an effect of Kinesio Tapping and Stretching Exercise on Changes in Flexibility in Low Back Pain Patients at Koesnadi Bondowoso Hospital. Based on the results of the study, it is recommended for further researchers to conduct research with a larger sample.